Glycyrrhiza Glabra (Advancements in Homeopathic Research, 2022)
Glycyrrhiza glabra Linn is a well-known medicinal plant used across the world for its medicinal value to cure varieties of ailments1.Glycyrrhizin is the major active constituent obtained from its roots, one of the most widely used in herbal preparations for the treatment and management of many chronic ailments3.It was introduced into homoeopathy in early 20th century and covered by German Homoeopathic Pharmacopoeia and Homoeopathic Pharmacopoeia of United States. Its medicinal properties and homoeopathic uses were discussed.
Keywords: Glycyrrhiza glabra; Glycyrrhizin; Homoeopathic uses; Liquorice; Medicinal plant